Navigating Educational Pathways for Sustainable Development: A Comparative Analysis of ALECSO and UNESCO in The Arab Region - Elamin , Mustafa Osman Ismail (International Journal of Membrane Science and Technology, 2023)
This comparative analysis delves into the educational strategies for sustainable development as employed by ALECSO and UNESCO within the Arab region. The study utilizes a mixed methods approach to dissect and compare the educational policies, strategies, and initiatives implemented by these two prominent organizations. Central to this examination is the contrast between ALECSO’s region-specific strategies, which are intricately designed to resonate with the cultural, political, and social fabric of the Arab world, and UNESCO’s more globally oriented approach, which is characterized by its adherence to international standards and norms. One of the study's critical arguments is the varying effectiveness of regionally tailored strategies versus globally standardized approaches in addressing the unique educational needs and sustainability goals of the Arab region. This is particularly evident in the way ALECSO’s initiatives are closely aligned with local contexts, possibly offering more practical and culturally sensitive solutions. In contrast, UNESCO’s strategies, while globally comprehensive, might not fully address specific regional nuances. The research further critiques the impact and effectiveness of the programs initiated by both organizations. This aspect is crucial in highlighting the strengths and weaknesses inherent in their respective approaches to promoting sustainable development through education. The study identifies key areas where ALECSO and UNESCO have succeeded, as well as areas where improvements are necessary. This critical assessment provides a nuanced understanding of how each organization contributes to the development of sustainable educational practices within the Arab region. Emphasizing the significance of contextually relevant educational strategies, the study advocates for adaptive and collaborative policymaking. This approach is posited as essential for enhancing the efficacy of future educational strategies for sustainable development, particularly in regions with distinct cultural and socio-political contexts like the Arab world. The findings of this study have broader implications, contributing significantly to the discourse on sustainable development in education. By offering in-depth insights into the roles and contributions of ALECSO and UNESCO, the study underscores the importance of aligning educational strategies with regional needs while also considering global sustainability goals.